1996
DOI: 10.1084/jem.183.3.949
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha and interleukin 1beta are responsible for in vitro myocardial cell depression induced by human septic shock serum.

Abstract: SummaryPrevious studies have demonstrated the presence of myocardial depression in clinical and experimental septic shock. This depression is associated with the presence of a circulating myocardial depressant substance with physical characteristics consistent with cytokines. The present study utilized an in vitro myocardial cell assay to examine the role of various human recombinant cytokines, including tumor necrosis factor (TNF)ot and interleukin (IL)113, in depression of cardiac myocyte contractile functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
346
1
6

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 677 publications
(371 citation statements)
references
References 37 publications
9
346
1
6
Order By: Relevance
“…Studies examining the basis of depressed myocardial contractility in sepsis showed that TNF-a and IL-1b impair cardiac and cardiomyocyte contractility (46)(47)(48). These cytokines also induce mitochondrial injury (44).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the basis of depressed myocardial contractility in sepsis showed that TNF-a and IL-1b impair cardiac and cardiomyocyte contractility (46)(47)(48). These cytokines also induce mitochondrial injury (44).…”
Section: Discussionmentioning
confidence: 99%
“…15 Because some of these cytokines are also released by adipocytes, we tested whether proinflammatory cytokines are responsible for the adipocyte-induced cardiodepressant effect. Concentrations of TNF-a, IL-6, IL-1b and IL-2 were measured in the AM and end concentrations in the experiment (dilution 1:6) were calculated (Table 1).…”
Section: Role Of Adipose Tissue In Cardiac Dysfunctionmentioning
confidence: 99%
“…An increased level of BNP and vasodilation in septic shock is a consequence of the cytokine production (9,25,26). Tumour necrosis factor-alpha and interleukin-1beta are important cytokines released during sepsis, which are associated with myocardial depression (25).…”
Section: Discussionmentioning
confidence: 99%